2017
DOI: 10.17221/276/2015-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant activities of some apple cultivars

Abstract: This study was conducted in order to determine the antioxidant activities of certain apple varieties. 'Galaxy Gala' , 'Scarlet Spur' , 'Fuji' , 'Pink Lady' and 'Granny Smith' were characterized in this study. The antioxidant activities among the varieties were determined via three different procedures. Antiradical activity figures of the apple varieties were between 0.592 ('Galaxy Gala') and 0.802 ('Scarlet Spur'). Inhibition levels of chelating activity with Fe +2 varied between 40.20-55.50%; 'Scarlet Spur' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…The amounts of total polyphenol content and antioxidant capacity differed among resistant apple cultivars and also among extraction methods (Figures 2-5). Several previous studies demonstrated that apple cultivars differed in their total polyphenol content or antioxidant capacity, e.g., [12,13,16,19,22,[51][52][53][54][55][56][57][58][59][60][61][62][63]. For instance, the study of Vieira et al [16] showed that the total phenolic content ranged between 128.3 and 212.0 mg GAE 100 g −1 dry matter among the investigated apple cultivars.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The amounts of total polyphenol content and antioxidant capacity differed among resistant apple cultivars and also among extraction methods (Figures 2-5). Several previous studies demonstrated that apple cultivars differed in their total polyphenol content or antioxidant capacity, e.g., [12,13,16,19,22,[51][52][53][54][55][56][57][58][59][60][61][62][63]. For instance, the study of Vieira et al [16] showed that the total phenolic content ranged between 128.3 and 212.0 mg GAE 100 g −1 dry matter among the investigated apple cultivars.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, this study was the first to show that antioxidant capacity of cultivars differed among extraction methods, which was not previously demonstrated for the four selected resistant apple cultivars. However, as many previous studies also noted, the chemical compositions of an apple cultivar may also be dependent on fruit maturity, growing area, agricultural and management practices, storage conditions, and environmental factors, e.g., [9,60,65].…”
Section: Discussionmentioning
confidence: 95%
“…Our results were higher than this data. Pirlak et al (2017) found that Galaxy Gala, Scarlet Spur, Fuji, Pink Lady and Granny Smith were determined TPC values between 18.29 and 26.83 mg GAE/g DW.…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 95%
“…The concentrations of polyphenols in apples are affected by many factors such as apple varieties, growing and storage conditions, sunlight, processing and the tissues of the fruit (Çolak and Özoğul, 2020;Drogoudi et al, 2008;Van der Sluis et al, 2001). So they are strongly associated with reducing the risk of agerelated human diseases such as cardiovascular diseases, several types of cancer, immune system decline, asthma, and type 2 diabetes due to the presence of antioxidant compounds protecting the cells against stress factors (Boyer and Liu, 2004;Pirlak et al, 2017;Sevindik et al, 2017). The cultivar is important in controlling the polyphenol composition of apples.…”
Section: Introductionmentioning
confidence: 99%
“…Apel memiliki kandungan yang dapat menghambat kerontokan rambut, diantaranya fitokimia seperti kuersetin, katekin, phloridzin, dan asam klorogenat. Kandungan procyanidin B-2 pada apel dapat meningkatkan aktivitas pertumbuhan sel folikel rambut dan merangsang perubahan siklus rambut [7] . Procyanidin B-2 memiliki aktivitas yang sama dengan minoksidil yaitu meningkatkan aktivitas pertumbuhan sel folikel rambut dan merangsang perubahan siklus rambut dari fase telogen menjadi fase anagen [8] .…”
Section: Pendahuluanunclassified